TRENDS IN THE DEVELOPMENT OF MODERN INTERNATIONAL RELATIONS. THE NEW CHALLENGES FOR DIPLOMACY (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The report analyzes the modern international system and the factors that influence its development. The impact of the Great Powers, the development of information technology and the impact of social media on the dynamics of international relations are considered. The imbalance of the system, provoked by the fundamentally different views of the main actors - the United States and Russia on the main issues, has increased over the years due to the lack of dialogue aimed at finding mutually acceptable conditions for its existence. There is an aspiration for multi-regionalization of the international system and the emergence of new "players" – China, India, the United Arab Emirates, Saudi Arabia and the Republic of Türkiye, which seeks to acquire the role of a regional balancer, including through existing regional conflicts, and in the Balkans to be a regional leader. The mosaic of modern international relations is characterized by the restructuring of connections within existing subsystems, which inevitably affects the degree of entropy of the entire system and its individual elements.